Routledge handbook of public diplomacy [ - Snow, Nancy; Taylor, Philip M.; Annenberg School of Communications (University of Southern California) . Center on Public Diplomacy (New York : Routledge, 2009)
Offers a comprehensive overview of the field of applied politics, encompassing political consulting, campaigns and elections, lobbying and advocacy, grass roots politics, fundraising, media and political communications, the role of the parties, political leadership, and the ethical dimensions of public life
"Published in association with the USC Center on Public Diplomacy at the Annenberg School based at the University of Southern California"
Description based on print version record
Includes bibliographical references (p 367-371) and index
Keywords: Diplomacy -- Handbooks, manuals, etc; International relations -- Handbooks, manuals, etc